49 The Annual Global Economic Burden of Heart Failure. (31st May 2014) - Cook, Christopher; Cole, Graham; Asaris, Perviz; Jabbour, Richard; Francis, Darrel
Abstract : Background: As the global problem of heart failure (HF) increases, there is also the significant economic burden of disease to be considered. It is vital for authorities to have an estimate of the costs attributed to HF, as they will have to plan, predict and finance the care of a rapidly growing and ageing global population. HF imposes both direct costs to healthcare systems and indirect costs to society through morbidity, unpaid care costs, premature mortality and lost productivity. The global economic burden of HF is not known. Methods: We estimated the overall cost of HF in 2012, in both direct and indirect terms, across the globe.A literature review of studies assessing the crude prevalence rates and economic burden of HF was performed. Data from government department of health documents, professional society reports and non-profit organisation reports were also included. HF costs analyses were converted from local currency into US dollars at the mean annual exchange rate for the year of study and expressed as a proportion of gross domestic product (GDP) and total healthcare spend. Using World Bank data, these proportional values were used to interpolate the economic cost of HF for countries of the world where no published data exists. Indirect costs were expressed as a percentage of GDP rather than total health expenditure, to better reflect the lost productivity through morbidity, premature mortality and welfare impact on others outside of allocated healthcare funds. Countries were categorised according to their level of economic development to investigate global patterns of spending. Results: 197 countries were included in the analysis, covering 98.7% of the world's population. Published economic estimates were predominantly from the USA, Europe and Australasia, with a resultant heavy bias towards high-income (n = 12) versus middle and low-income (n = 1) countries of study. The overall economic cost of HF in 2012 was estimated at 108 billion per annum. Direct costs accounted for 60% (65 billion) and indirect costs accounted for 40% (43 billion) of the overall spend. Global per capita spending in 2012 was approximately 24/annum. HF spending varied widely between high-income and middle and low-income countries.High-income countries spent a greater proportion on direct costs: a pattern reversed for middle and low-income countries. A gross imbalance in terms of per capita spending between world economic regions reflects a situation where the global majority of patients with HF are unable to access optimal HF care. Conclusions: This study defines the global economic impact of HF. It provides a benchmark value intended to develop understanding of the impact of HF outside of the conventional framework of mortality and morbidity. HF imposes a huge economic burden, estimated at 108 billion per annum. With an ageing, rapidly expanding and industrialising global population this value will continue to rise.